Exosomal circular RNA hsa_circ_007293 promotes proliferation, migration, invasion, and epithelial–mesenchymal transition of papillary thyroid carcinoma cells through regulation of the microRNA-653-5p/paired box 6 axis. Issue 2 (20th December 2021) - Lin, Qiuyu; Qi, Qianle; Hou, Sen; Chen, Zhen; Jiang, Nan; Zhang, Laney; Lin, Chenghe
ABSTRACT: Circular RNAs (circRNAs) or exosomes have been reported to exert key regulatory and/or communication functions in human cancer. Nevertheless, current literature on the effects of exosomal circRNAs on tumor invasion and metastasis in thyroid cancer is incomplete. The role of tumor-derived exosomes in driving in vitro papillary thyroid carcinoma (PTC) progression and metastasis requires further investigation. In our study, Exosomes were harvested from PTC patient serum and PTC cell culture medium. Gene expression analysis in PTC cell lines and exosomes was performed with quantitative reverse-transcription polymerase chain reaction. Transwell, wound healing, Western blot assays, and the cell counting kit-8 were applied for functional analysis. Dual-luciferase reporter assay was used to examine the interaction between hsa_circ_007293 (circ007293), microRNA (miR)-653-5p, and paired box 6 (PAX6). Results showed that circ007293 was enriched in exosomes derived from PTC patient serum and cell culture media. Moreover, circ007293 could enter PTC cells through exosomes, and exosomal circ007293 promoted PTC cell epithelial–mesenchymal transition, invasion, migration, and proliferation. circ007293 knockdown reversed the malignant phenotype of PTC cells in vitro . Additionally, circ007293 could competitively bind with miR-653-5p to regulate PAX6 expression. Notably, miR-653-5p overexpression or PAX6 inhibition suppressed the malignant effects of exosomal circ007293. These results evidenced that exosomal circ007293 induced EMT and augmented the invasive and migratory abilities of PTC cells via the miR-653-5p/PAX6 axis, suggesting that it may serve as a promising biomarker for cancer progression.